Prevalence of external injuries in small cetaceans in Aruban waters, southern Caribbean. - Jolanda A Luksenburg (PLoS ONE)
Aruba, located close to the coasts of Colombia and Venezuela, is one of the most densely populated islands in the Caribbean and supports a wide range of marine-related socio-economic activities. However, little is known about the impacts of human activities on the marine environment. Injuries in marine mammals can be used to examine interactions with human activities and identify potential threats to the survival of populations. The prevalence of external injuries and tooth rake marks were examined in Atlantic spotted dolphin (Stenella frontalis) (n = 179), bottlenose dolphin (Tursiops truncatus) (n = 76) and false killer whale (Pseudorca crassidens) (n = 71) in Aruban waters using photo identification techniques. Eleven injury categories were defined and linked to either human-related activities or natural causes. All injury categories were observed. In total, 18.7% of all individuals had at least one injury. Almost half (41.7%) of the injuries could be attributed to human interactions, of which fishing gear was the most common cause (53.3%) followed by propeller hits (13.3%). Major disfigurements were observed in all three species and could be attributed to interactions with fishing gear. The results of this study indicate that fishing gear and propeller hits may pose threats to small and medium-sized cetaceans in Aruban waters. Thus, long-term monitoring of population trends is warranted. Shark-inflicted bite wounds were observed in Atlantic spotted dolphin and bottlenose dolphin. Bite wounds of cookie cutter sharks (Isistius sp.) were recorded in all three species, and include the first documented record of a cookie cutter shark bite in Atlantic spotted dolphin. This is one of the few studies which investigates the prevalence of injuries in cetaceans in the Caribbean. Further study is necessary to determine to which extent the injuries observed in Aruba affect the health and survival of local populations.